2008
DOI: 10.14712/18059694.2017.2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Luting Agents on the Marginal Discrepancy of Procera® AllCeram Alumina Crown Copings – An Experimental Study

Abstract: Summary: Two maxillary first molars and two central incisor typhodont teeth were prepared with 0.8 mm chamfer, 2.0 mm occlusal reduction, and 6 degree taper. The prepared teeth were duplicated 9 times to obtain 36 die stone models and divided into three groups (n = 12). Luting agents tested were zinc phosphate, glass ionomer and resin cement. Procera ® AllCeram 0.6 mm coping was fixed with a calibrated finger force of 50 N. The absolute marginal discrepancy was measured using the scanning electron microscope o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…In the present study, cast copings cemented with zinc phosphate showed significantly higher VMD values. These results are according to those of previous studies [ 20 , 21 ] which concluded that zinc phosphate cement showed the highest film thickness compared with glass ionomer and polycarboxylate and may be attributed to its increased viscosity. Abutment geometry and luting agent statistically influenced the VMD of the evaluated cast copings.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, cast copings cemented with zinc phosphate showed significantly higher VMD values. These results are according to those of previous studies [ 20 , 21 ] which concluded that zinc phosphate cement showed the highest film thickness compared with glass ionomer and polycarboxylate and may be attributed to its increased viscosity. Abutment geometry and luting agent statistically influenced the VMD of the evaluated cast copings.…”
Section: Discussionsupporting
confidence: 92%
“…The marginal accuracy of the cemented crown is of clinical importance and influences long-term survival of the restorations (20) . Marginal fit of complete crown restorations and different cementation techniques influence definitive seating of the cemented prosthesis affecting not only periodontal status but also longevity (21) .The luting agents may influence the marginal discrepancy values by elevating the crown after cementation (22) .In this study, zinc phosphate had a larger mean marginal gap than the other three types of cements.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, various values have been proposed in the literature as the maximally acceptable marginal gap (20) Heba Mohamed Ahmed, et al…”
Section: Discussionmentioning
confidence: 99%